New species of the feather mite genus Protolichus Trouessart, 1884 (Astigmata, Pterolichidae) from lories and lorikeets (Aves: Psittaciformes) - Mironov, Sergey V.; Ehrnsberger, Rainer; Dabert, Jacek (Zootaxa, 2014)
Five new species of the feather mite genus Protolichus Trouessart, 1884 (Astigmata, Pterolichidae) are described from parrots of the subfamily Loriinae (Psittaciformes: Psittacidae): Protolichus ornatus sp. n. from Trichoglossus ornatus (Linnaeus, 1758), P. lorinus sp. n. from Lorius lory (Linnaeus, 1758), P. placentis sp. n. from Charmosyna placentis (Temminck, 1835), P. pulchellae sp. n. from C. pulchella (Gray GR, 1859), and P. rubiginosus sp. n. from T. rubiginosus (Bonaparte, 1850). Protolichus ornatus belongs to the brachiatus species group; the other new species belong to the crassior species group.